The Age of Machines: Anders on Work, Alienation and Promethean Gap - Monaro, Federico (Philosophy and Realistic Reflection, 2025)
This article examines Günther Anders’s critical reflection on the human condition in technological modernity, focusing on the central concepts of the “obsolescence of man” and the Promethean Gap. The latter describes the widening disproportion between the productive power of machines and the limited cognitive, moral, and imaginative capacities of human beings. Anders argues that this imbalance generates alienation, disorientation, and even shame in relation to our own creations, as exemplified by the nuclear threat, which vastly exceeds our ethical preparedness to confront its consequences. Drawing on Marx and Heidegger, the article highlights how industrialization and automation have reshaped the sphere of labor, stripping it of creativity and meaning, and transforming human beings into passive supervisors of processes they can neither master nor fully comprehend. Alienation, once limited to the factory, increasingly permeates everyday life, producing a condition in which individuals experience themselves as inadequate when compared with the efficiency, durability, and autonomy of machines. Anders’s critique shows that technology is not a neutral instrument, but a social and political force that incorporates logics of domination and subordination, demanding adaptation at the cost of freedom and subjectivity. His work also anticipates contemporary debates on artificial intelligence, automation, and ecological collapse, underscoring the urgent need for new ethical and political frameworks capable of guiding human action in a technological age. By exposing the risks of a society that uncritically celebrates technical progress, Anders calls for renewed human agency rooted in responsibility, foresight, and resilience.